Pengaruh Sistem Pengendalian Mutu dan Kompetensi Auditor Dalam Meningkatkan Kualitas Audit - David HM Hasibuan; Vanny Silviana Wijaya (Jurnal Ilmiah Akuntansi Kesatuan, 2020)
The increasing number of public accounting firms in Indonesia certainly creates very tight competition among public accounting firms in getting clients. With the existence of the cases related to external auditors, it is very natural that companies become very critical in selecting public accounting firms. To overcome this, public accounting firms and public accountants need to improve their audit quality in order to produce relevant and reliable information so as to make accounting information useful in making decisions. This research aims to analyze the effects of the quality control system and auditor competence in improving audit quality on public accountant auditors in Jakarta. The research method used in this research was descriptive research with a quantitative approach. The population was all public accountant auditors registered in Directory AP & KAP 2019 in the Jakarta area compiled by the Indonesian Institute of Certified Public Accountants (IAPI). The sampling technique was convenience sampling. The type of data was primary data using a questionnaire as a primary data collection method. The data analysis technique was the statistical analysis method using the SPSS program. The processing method was multiple linear regression analysis. The results show that partially there is a positive and significant effect of the quality control system (significance value of 0,000 < 0,05 and t count value of 5,995 > 1,969) and auditor competence (significance value of 0,000 < 0,05 and t count value of 8,859 > 1,969) in improving audit quality on public accountant auditors in Jakarta. Moreover, the results of this research also indicate that there is a positive and significant effect of the quality control system and auditor competence simultaneously in improving audit quality on public accountant auditors in Jakarta, which is illustrated by a significance value of 0,000 < 0,05 and F count value of 173,519 > 3,029. Keywords: Quality Control System, Auditor Competence, Audit Quality